Design and control of a cascaded boost converter - Ong, Vincent Choong Shin (2014)
Recent technologies have seen an increased demand in portable devices. This led to an increased demand for converters such as the DC-DC cascaded boost converter. Such converters have the ability to generate high voltage on a single battery in each device. This report presents the circuit design, implementation and control of a two-stage cascaded boost converter with a single switch using current mode control. The boost converters were used to step up a low input DC voltage to a higher output voltage. The input currents and output voltage were regulated using a current mode based controller. This project makes a comparison between the input current of two inductors in order to determine which inductor yields a better result in regulating the desired output voltage. Experimental results are also provided to show the closed-loop performance for each inductor's input current.